Developing instrument of academic potential test analogy verbal ability for undergraduate students - Efi Septianingsih; Mohammad Adam Jerusalem (Intelektual Pustaka Media Utama, 2021)
The paper aims to develop the instrument about analogy test to measure the level of intelligence of undergraduate students. Determination of the number of samples is done by purposive sampling technique. This instrument is analyzed by factor analysis. Of the 15 items that will be used to develop the academic potential test instrument for verbal analogies, 4 analysis factors. The formation of these 4 factors is from Eigenvalues greater than 1 so that there are only 4 factors that fulfill the requirements. Furthermore, 15 items of the tested instrument to 91 undergraduate student respondents obtained 2 items of invalid instrument with correlation coefficient ≤0.3, Kaiser-Meyer-Olkin (KMO) and Bartlett's test amounted to 0.785 with p less than 0.05. Trial results from the results of the trial results obtained that the average validity of the questions is 96.8%. Test reliability was analyzed using the Alpha (α) formula of Cronbach. The calculation is done using the help of the IBM SPSS version 22.0 Windows program and the coefficient of 0.806 is obtained. Based on the results of the research, it can be concluded that the quality of the developed instrument items has been valid and reliable.